2018
DOI: 10.21776/ub.jiip.2018.028.01.03
|View full text |Cite
|
Sign up to set email alerts
|

Kasus mastitis sub klinis pada sapi perah laktasi di Kecamatan Pujon Kabupaten Malang

Abstract: ABSTRAK : Penelitian ini bertujuan untuk megetahui jumlah kasus mastitis subklinis di Kecamatan Pujon, Kabupaten Malang. Penelitian ini dilakukan di Kabupaten Pujon Kabupaten Malang dengan menggunakan metode survei. Kriteria peternak yang dipilih minimal sudah 2 (dua) tahun memelihara sapi perah. Sebanyak 110 ekor sapi perah laktasi dari Dusun Maron Sebaluh Desa Pandesari dan 103 ekor sapi perah Dusun Bakir di Desa Sukomulyo diperiksa terhadap mastitis subklinis dengan menggunakan Uji Mastitis California (CMT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
1
3
0
1
Order By: Relevance
“…In our data, SCM cases were reported in all studies (n = 37),whereas CM was reported in only six studies among all sources. Accordingly, the SCM prevalence in dairy animals was significantly higher than the CM prevalence in Indonesia, which is similar to the global trend [55]. However, the prevalence of SCM in Indonesia (58.24%) was higher than that observed worldwide (42%), in India (45%), in Ethiopia (32.21%), and in China (37.7%) [1,3,57,58].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…In our data, SCM cases were reported in all studies (n = 37),whereas CM was reported in only six studies among all sources. Accordingly, the SCM prevalence in dairy animals was significantly higher than the CM prevalence in Indonesia, which is similar to the global trend [55]. However, the prevalence of SCM in Indonesia (58.24%) was higher than that observed worldwide (42%), in India (45%), in Ethiopia (32.21%), and in China (37.7%) [1,3,57,58].…”
Section: Discussionsupporting
confidence: 71%
“…A total of 735 studies were retrieved and subjected to the screening process, including 37 studies with 6050 samples, ranging from 30 to 592 in the selected articles. Figure-1 presents the selection process, and Table-1 shows the characteristics of the included studies [ 19 55 ]. Based on the province, almost all of the studies were conducted in Java Island (East Java, n = 22; West Java, n = 5; Central Java, n = 5; Yogyakarta, n = 4), and two were conducted in Riau and North Sumatera.…”
Section: Resultsmentioning
confidence: 99%
“…The high prevalence in Oceania may be due to the low number of studies conducted there, the high prevalence of subclinical mastitis observed in these studies and the inclusion of Indonesia in Oceania. In some of the studies, the prevalence of subclinical mastitis in Indonesia was calculated as 85.33% (Effendi et al 2018) and as 58.18% (Zalizar et al, 2018). Krishnamoorthy et al (2021) calculated the prevalence of subclinical mastitis in the continents of Asia, Europe and Oceania as 42%, 37% and 36%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Periode atau selang waktu seekor sapi setelah beranak (partus) sampai dikawinkan kembali hingga terjadinya kebuntingan (Wardhani et al, 2015).…”
Section: Lama Masa Kosong (Length Of Days Open)unclassified